"CIEMNA LICZBA" PRZESTĘPSTW. PRZYKŁAD BADAŃ WIKTYMIZACYJNYCH MIESZKAŃCÓW WYBRANYCH OBSZARÓW W ŁODZI - Mordwa, Stanisław (Space – Society – Economy, 2012)
In Poland, only about one in two crimes is reported to police, but there is an another type of data source that shows the rest of crimes. By directly questioning victims about their experiences, it is possible to generate information about the socalled dark figure of crime, i.e. about those incidents that go either unreported or unrecorded by the police. The paper presents the analysis of the researches on the dark figure of crime of three selected housing estates in Łód : D browa (tower blocks), Julianów (single housing) and Nowe Miasto (downtown). Various parts of the paper analyze the research results on reporting rate and risk of victimization. The socio-demographic characteristics of residents which influence the level of fear were also studied. The survey also confirmed a correlation between the sense of security and the level of unrecorded crime. The residents of Nowe Miasto, for example, lowly assess their personal security (although it has the average recorded crime rate) because of the highest victimization rate.